Te Karanga Ki Ngākengake The Call of the Shifting Forces - Hannah Hopewell; Matthew Wakelin (Landscape Review)
This design proposal extends and intensifies the powerfully present geological conditions of Te Whanganui-a-Tara–Wellington’s harbour. Originally conceived for an international design competition it contextualises the magnitude of geologic time and imagines an embodied experience of suspension, a quality of being between worlds yet in the felt immediacy of nothing but kenetic change. The design emerges from and is given meaning by Te Ātiawa pūrākau of taniwha Ngake and Whātaitai. Together these taniwha give the why and how of Pōneke Wellington’s land and seascape; they contextualise geomorphology in deep time and express the entangled alliance between mana whenua and the specificity of place, a quality defining Pōneke Wellington. With the design we touch into multiple relational intersections made possible by the forever mercurial space where the sea and the land meet, yet do so in such a way to unsettle settler colonial schemas of landscape-seascape experience.